Analysis of Mobile Banking Acceptance in Indonesia using Extended TAM (Technology Acceptance Model) - Andhika, Imam; Pratama, Ahmad R; Pratama, Yogi (Universitas Negeri Padang, 2023)
The use of Communication and Information Technology which is developed through the years is one of the key of organization’s success in business rivalry through pandemic era nowadays. In line with the development of technology and information, bank authorities also offer the facility of banking through mobile banking (m-banking) application that can be accessed by using smartphone. This research aims to analyze factors that can influence the acceptance of m-banking application in Indonesia. The data was gathered through survey of 412 m-banking users in Indonesia and it was analyzed by using Structural Equation Modeling (SEM) with Extended Technology Acceptance Model (TAM). The findings of the research showed positive attitudes, perceived usefulness and perceived ease of use felt by the m-banking users and become the main reasons in adopting this technology besides social influence and perceived risk of m-banking technology. Meanwhile, the fear of using technology in using m-banking technology has a potential to obstruct the technology adoption. The result of this research can help the bankers and stakeholder in formalizing strategical steps in improving the adaptation of m-banking technology and application, especially in Indonesia.